Electrochemical synthesis and magnetic characterization of periodically modulated Co nanowires - Minguez Bacho, Ignacio; et al. (Nanotechnology, 2014)
The synthesis of templates with modulated pore channels by combined mild and hard anodization processes is described. The hard anodization pulses, implemented during anodization, are controlled not only in time length and amplitude, but also in shape: square and exponential signals have been applied. Electrodeposition of Co is subsequently performed to obtain uniform and modulated diameter nanowire arrays. Square and exponential modulated diameter nanowires are imaged by scanning electron microscopy and hcp hexagonal polycrystalline structure is confirmed in all Co nanowires. Magnetic behavior strongly depends on nanowire shape and is interpreted considering the modification of magnetostatic interactions between wires induced by local stray fields from magnetic charges at the ends of the wider segments in modulated wires. As a consequence, magnetization processes under parallel and perpendicular field configurations denote the contribution of both thin and wide segments.
Keywords: modulated diameter nanowires; Co nanowire arrays; anodic alumina; hard anodization; structural and magnetic characterization